Texture Studies on Chromium Oxide Doped Catalysts - K.M. Abd El-Salaam; A.M. El-Awad (Adsorption Science & Technology, 1987)
Physisorption of N 2 gas at 77 K has been used to determine the surface area (SBET) and porosity of Cr 2 O 3 impregnated with Li 2 O in molar ratios extending from 0.25 to 50 mol %. Calcination of catalysts was affected in air flow in temperature range of 473-773 K. Variation of the SBET-calcination temperature relationship was interpreted according to the possible lattice rearrangements via a solid-state reaction leading to Li 2 CrO 4 phase formation for Li 2 O rich samples and by creation of cation vacancies in case of Li 2 O trace samples. The cumulative calculations together with Va-t plots showed a mesoporous surface nature of samples.